ANALISIS EVALUASI PROGRAM PEMBERDAYAAN NELAYAN TANGKAP DI PELABUHAN PERIKANAN NUSANTARA (PPN) KARANGANTU KOTA SERANG - Ipah Ema Jumiati (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2018)
The research focused on fishering empowering program implemented in The National Fishery Harbor of Karangantu at Serang City in 2012 and 2013. Which are not properly done after doing the assesment of program results. This condition causes the evaluation results by the program evaluator can not be used as a benchmark in preparing a better decision recommendation. The theory used as a foothold is Jones's Evaluation Program theory (1984: 199): specification, assessment, analysis and recommendations. The paper focuses on the third step of analysis, through qualitative approaches using case studies that aim to describe, summarize the various conditions, various situations or various phenomena of social reality of society. Based on economic and social considerations that the evaluation is not looking at the socio-cultural conditions that take place in Karangantu, then the dependence on technical guidance is very high, so the initiatives of fishing communities rarely come to the forefront. Recommendation of this research is still needed role of Technical Team and Fisheries Supporting Extension as facilitator and evaluator in program evaluation. Moreover the main task as a program implementer at the community level. Then the Facilitator and Evaluator are expected to have educational qualifications, experience and insight in the field of community empowerment, and have a high commitment and partisanship towards the poor.